Reducing STD/HIV stigmatizing attitudes through community popular opinion leaders in Chinese markets - Rice, Ronald E. (2012)
Reducing STDs and HIV/AIDS incidence requires campaigns designed to change knowledge, attitudes and practices of risky sexual behavior and its consequences. In China, a significant obstacle to such changes is the stigma associated with these diseases. Thus one campaign intervention strategy is to train credible community popular opinion leaders to discuss these issues in everyday social venues. This study tested the effectiveness of such an approach on reducing HIV/AIDS stigma, across two years, from a sample of over 4500 market vendors, in three conditions. Results showed an increasing growth in market communication about intervention messages, and concomitant declines in stigmatizing attitudes, across time, with the greatest changes in community popular opinion leaders, significant changes in intervention non-opinion leaders, and little change in the control markets.